Global Existence of the Cylindrically Symmetric Strong Solution to Compressible Navier-Stokes Equations - Jian Liu; Ruxu Lian (Abstract and Applied Analysis)
This paper is concerned with the initial boundary value problem for the three-dimensional Navier-Stokes equations with density-dependent viscosity. The cylindrically symmetric strong solution is shown to exist globally in time and tend to the equilibrium state exponentially as time grows up.